A novel adjuvant : polymerised serum albumin beads - Dewar, John Barr (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1985)
Lee, T. et al (1981) proposed the encapsulation of hormones such as progesterone into serum albumin beads, such that their in vivo proteolysis would allow a gradual release of hormone at low levels, for extended hormone action. It was proposed, in the Department of Microbiology, Rhodes University, to replace the hormone component of the above bead formulation, with virus as antigen, in the development of a vaccine. Beads optimally crosslinked at 1% final glutaraldehyde concentration, containing Nodamura virus, were shown to promote an adjuvant effect in vivo, analogous to the release of antigen from Freund's Complete Adjuvant (FCA), so that extended immunostimulation resulted. It was shown that soluble antigen promoted a short-lived primary immune response, peaking around day 25 following inoculation. Antigen presented in beads, on the other hand, initially elicited a low humoral response, but this response gradually increased up to a peak around day 110 post inoculation, before decreasing. No apparent adverse side-effects were noted following inoculation of antigen-containing serum albumin beads, compared to necrosis following antigen in FCA inoculation, supporting the proposal of using albumin homotypic for the test inoculee animal, so that the beads would themselves be non-immunogenic and would merely act as a vehicle in the vaccine formulation. The indirect enzyme-linked immunosorbent assay (ELISA) was used to monitor the humoral response to antigen following inoculation. Results showed that covalent crosslinking of albumin in the formation of the beads did not promote immunogenicity on the part of the chemically altered albumin. The ELISA test was used to indicate the kinetics of the IgG response to Nodamura virus when presented in formulations such as: Freely soluble virus or its subunit; soluble intact virus inactivated by treatment with glutaraldehyde; intact virus entrapped in serum albumin beads cross; linked at different percentage final glutaraldehyde concentrations and also virus subunit prepared in albumin beads. The presence of virus-neutral ising antibodies was noted in serum obtained from rabbits inoculated with virus entrapped in albumin beads. Virus infectivity, titrated in mice, showed protection against virus challenge after incubation of virus with serum obtained above.
Keywords: Antigens; Serum albumin